The sustainability of dairy development in Tanzania: Adoption of a Participatory Market Chain Approach System - Muchichu, R.N. (University of Queensland, 2014)
This study looked at the sustainability of dairy development in Tanzania. Ongoing dynamic changes in the global dairy industry have progressively put a strain on smallholder farmers. Changes in competition patterns, consumer preferences and market requirements are likely to see smallholder farmers further marginalised in the dairy production. The question remains how to ensure these smallholder farmers remain competitive and agile in the fast moving industry. This research looks at the adoption of an intervention program that aims to include smallholder farmers in rural Tanzania into modern value chains. A survey of 96 participants (65 input providers and 31 traders) was done and analysed using Partial Least Squares regression to determine the effects of the harsh market conditions on the participants’ behavior control and intention as well as on the new programs incentives. In one sample-set, the harsh market conditions positively influenced the incentives indicating an awareness of likely gain from the harsh market. In the second sample-set, the harsh market conditions positively influenced motive indicating an expectation from participants that the conditions will be addressed by the intervention program. Both motive and incentives influenced intention to participate in sample 2 while only incentives influenced intention in sample 1.